2011
DOI: 10.1002/ps.2112
|View full text |Cite
|
Sign up to set email alerts
|

Composition of essential oil of Chinese Chenopodium ambrosioides and insecticidal activity against maize weevil, Sitophilus zeamais

Abstract: The findings suggested that the essential oil of Chenopodium ambrosioides and its main active constituent, (Z)-ascaridole, may be explored as a natural potential fumigant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 40 publications
3
56
1
5
Order By: Relevance
“…In another study, crude volatile oils and active phytoconstituents (Z)-ascaridole from C. ambrosioides were tested against the maize weevil Sitophilus zeamais to get the better natural fumigant. From the result, it was found that the essential oil of C. ambrosioides and their main active constituent (Z)-ascaridole could be used as a natural potential fumigant [30].…”
Section: Effect Of Ascaridole As Potential Fumigantmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, crude volatile oils and active phytoconstituents (Z)-ascaridole from C. ambrosioides were tested against the maize weevil Sitophilus zeamais to get the better natural fumigant. From the result, it was found that the essential oil of C. ambrosioides and their main active constituent (Z)-ascaridole could be used as a natural potential fumigant [30].…”
Section: Effect Of Ascaridole As Potential Fumigantmentioning
confidence: 99%
“…Optical activity and chromatographic resolution of naturally occurring ascaridole and several synthetic derivatives were evaluated and the results showed that C. ambrosioides and Peumus boldus produce have ascaridole in racemic form [47]. GC-MS method was used for the determination of the essential oil composition of the C. ambrosioides prepared through hydrodistillation process and five active components ρ-cymene, 2-carene, (Z)-ascaridole, iso-ascaridole and α-terpinene were found to be present in the C. ambrosioides [30]. In another study, ascaridole and other monoterpene hydroperoxides were isolated from C. ambrosioides and further the structures of these monoterpenes were determined through spectroscopic methods and chemical correlations [19].…”
Section: Analytical Aspect Of Ascaridolementioning
confidence: 99%
“…Some monoterpene compounds, such as ascaridole, carvarcrol, p-cymene, limonene and α-terpinene, has been identified as the major constituents of C. ambrosioides L. extract (Olajide et al, 1997;Cavalli et al, 2004;Jardim et al, 2008) and their biological activities, which contained the antibacterial, the antifungal, the insecticidal and the repellent activities, have been reported (Jardim et al, 2008;Chu et al, 2011;Monzote et al, 2014;Pandey et al, 2014). These studies suggest that C. ambrosioides L. extract is the potent crop protection material.…”
Section: Research Articlementioning
confidence: 99%
“…However, excessive use of synthetic fumigants and insecticides has several detrimental effects, including but are not limited to insecticide resistance, environmental contamination, and damage to human health and other non-target organisms [2,3]. Research into alternative treatments has shown that essential oils and their constituents possess insecticidal properties against many stored-product insect pests [4][5][6]; therefore, these may be alternatives to currently used fumigants and insecticides.…”
Section: Introductionmentioning
confidence: 99%